A Qualitative Analysis on Pesantren Economic: NVivo Approach - Nadia Nurul Izza; Denizar Abdurrahman Mi'raj (SMART Insight, 2023)
Based on a report from the Ministry of Religion, West Java is one of the provinces that contributes the most number of Pesantren, namely 8,343 Pesantren or about 30.92 per cent of the total national Pesantren. This shows that pesantren, as an institution with entrepreneurial characteristics, can contribute to the concept of a sustainable business by providing benefits from the social, economic and environmental aspects. This study aims to determine the economic development of Pesantren in the last 21 years, from 2001 to 2022. The method used is a qualitative analysis of secondary data in the form of metadata with the keywords pesantren economics from 403 Dimensions.ai indexed publications, then processed using Nvivo 12 Plus software. The results showed that the number of publications on the economic development of Pesantren continued to increase. From the results of the exploratory review and visualization of the pattern of pesantren economic themes, it was found that there were four research lines with discussions on pesantren and community empowerment, pesantren and cooperatives, pesantren and entrepreneurship, as well as pesantren and Micro Waqf Bank (BWM). In addition, this study shows that most of the research on the economics of Pesantren is related to the words economic, business, management, development, and program. As for the business management system and its development, it is still a challenge for pesantren. Thus, this research can be used as an essential reference to see how the graphic visualization of the development of research trends with the theme of Islamic boarding school economics in published scientific research so that experts can further develop it. This research is expected to help expand academic studies related to the economics of Pesantren.